Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing - Cadahía, Estrella; Conde, Elvira; Fernández de Simón, Brígida; García-Vallejo, María Concepción (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360doi: 10.1021/jf9709360The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; ellagitannins; high performance liquid chromatography; polyphenols; proanthocyanidins; Quercus suber; Tannins

Changes in Tannic Composition of Reproduction Cork Quercus suber throughout Industrial Processing (Journal of Agricultural and Food Chemistry, 1998)
Tannic composition was studied in reproduction cork samples from three different trees of Spanish Quercus suber and at different industrial processing stages. The ellagitannins, roburins A and E, grandinin, vescalagin, and castalagin, were identified and quantified by HPLC. Global evaluations of tannins were also carried out, using classical chemical methods. The group of hydrolyzable tannins was the most abundant in the tannic extract in all samples; among them, castalagin was the main component, followed by vescalagin, grandinin, roburin E, and, to a much lesser extent, roburin A. The changes in tannic composition throughout the industrial processing are mainly related to the boiling process and are more pronounced in total phenol and proanthocyanidin contents than in individual ellagitannins content. Vescalagin and roburins A and E were selected as those variables that provided the greatest discrimination among stages. Important differences in the ellagitannin contents were observed among the trees studied, all of the ellagitannins being discriminant variables in this case. Keywords: Quercus suber; cork; tannins; ellagitannins; proanthocyanidins; polyphenols; high-performance liquid chromatography
doi: 10.1021/jf9709360